The manager's pocket guide to effective mentoring - Cohen, Norman (HRD Press, 1999)
This book is a practical reference to effective mentoring in a format that provides quick access to the important concepts and techniques of this unique, powerful, one-to-one learning model. The Manager's Pocket Guide to Mentoring is a convenient and comprehensive reference, offering valuable, pragmatic guidance that mentors can use in assisting mentees to: Participate in constructive interpersonal dialogues during the mentoring experience; Map out attainable personal and professional goals; Analyze problems, formulate realistic solutions, and make constructive decisions; Plan workable strategies for promoting career, training, and educational development; Initiate positive actions to achieve stated objectives. This guide presents an expanded view of the behavioral expertise required of today's mentors who are faced with the challenge of establishing and sustaining mentoring relationships within more complex workplace, academic, and social environments.
Title from title screen. - Includes index
Keywords: Mentoring in business -- Handbooks, manuals, etc; Employees -- Counseling of; Personnel management -- Handbooks, manuals, etc; Mentorat dans les affaires; Guides, manuels, etc; Personnel; Counseling; Personnel; Direction; Guides, manuels, etc; BUSINESS & ECONOMICS; Training; BUSINESS & ECONOMICS; Mentoring & Coaching; Employees; Counseling of; Mentoring in business; Personnel management; handbooks; Handbooks and manuals; Guides et manuels